2023
DOI: 10.3390/mi14020369
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experimental Investigation of an Ultra-Low Frequency, Low-Intensity, and Multidirectional Piezoelectric Energy Harvester with Liquid as the Energy-Capture Medium

Abstract: Traditional piezoelectric vibration energy harvesters (PVEHs) usually adopt a rigid energy-capture structure, which can achieve efficient energy harvesting in single-directional, high-frequency, and high-intensity vibration environments. However, efficient harvesting with the use of low-frequency, low-intensity, and multidirectional vibration energy remains a challenge for existing harvesters. To tackle this problem, we proposed a PVEH with liquid as the energy-capture medium. Our previous research verified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…It has been proved that a quarter-circular arc piezoelectric beam can harvest vibration energy in three directions [ 29 ]. Based on the conventional cantilever–pendulum approach, Qin’s group used liquid as the energy-capturing medium to simultaneously achieve ultralow frequency, low intensity and multidirectional energy harvesting [ 30 , 31 ]. The liquid was stirred using horizontal or vertical vibrations, and the induced waves were sensed by the floater–lever array to bend the piezoelectric beam.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that a quarter-circular arc piezoelectric beam can harvest vibration energy in three directions [ 29 ]. Based on the conventional cantilever–pendulum approach, Qin’s group used liquid as the energy-capturing medium to simultaneously achieve ultralow frequency, low intensity and multidirectional energy harvesting [ 30 , 31 ]. The liquid was stirred using horizontal or vertical vibrations, and the induced waves were sensed by the floater–lever array to bend the piezoelectric beam.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has suggested the use of ferrofluids not as the transduction element but as a lubricant in solid magnet energy harvesters [ 19 ]. Other types of liquid-type energy harvesting devices utilize thermal gradients [ 20 ], which serve as an indirect way of vibration energy harvesting using various types of thermo-mechanical principles such as pyroelectric [ 21 ] and piezoelectric [ 22 ] effects. Utilizing mechanical vibrations from thermal gradients has been recently explored by Wang et al, which looks at developing an analytical model for electromagnetic induction in pulsating ferrofluid pipe flows [ 23 ], which has been validated against experimental data collected by Monroe et al [ 24 ].…”
Section: Introductionmentioning
confidence: 99%